The Influence Of The School Environment, Parental And Peer Support On Increasing The Learning Motivation Of Students Of Insan Islamic Junior High School Kamil An-Nahdliyah Wonoayu Sidoarjo - Ramadhani Zalsanudin, Virgie; Masfufah, Masfufah; Kholidatur Rodiyah, Siti (Molang: Journal Islamic Education, 2026)
Problems in the education system make the low quality of education in Indonesia less than optimal. The low quality of education in junior high school can be seen from the lack of motivated students in learning activities. A student of SMP Islam Insan Kamil An-Nahdliyah Wonoayu Sidoarjo gave a little overview of the influence of problems that befall the quality of education in Indonesia that is not optimal. Factors that cause imbalances in education in Indonesia result in an uneven education system and learning objectives that cannot be achieved optimally. The importance of support from various parties is expected to be able to help in achieving the learning goals that have been made. This study aims to determine the significant influence of the school environment, parental support, and peers on increasing student learning motivation SMP Islam Insan Kamil An-Nahdliyah Wonoayu Sidoarjo. This study uses a quantitative survey method with a population of seventy five students and is used as a sample as a whole. The sampling technique uses nonprobability sampling with the total sampling method. Data analysis techniques through data quality tests, classical assumption tests and multiple linear regression tests. The results of this study found that the school environment did not have a significant effect on increasing student learning motivation, parental support have a significant positive effect on increasing students' motivation to learn, and peers do not have a significant effect on increasing students' motivation.